Science and Providence : God's Interaction with the World. - Polkinghorne, John C. (Templeton Press, 2008)
Internationally renowned priest-scientist Dr. John C. Polkinghorne examines whether a personal, interacting God is a credible concept in today's scientific age. Encouraging the belief that there is a compatibility between the insights of science and the insights of religion, this book, previously published in the United Kingdom, focuses on the viewpoint that the world is one in which both human beings and God have the freedom to act.A modern understanding of the physical world is applied to questions of prayer and providence, such as: Do miracles happen? Can prayer change anything?